2022
DOI: 10.1111/iej.13784
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of endodontic tissue engineering in treatment of apical periodontitis: A systematic review

Abstract: Background: Regenerative endodontics has evolved in recent years with tissue engineering concepts in particular appearing promising. Endodontic tissue engineering (ETE) describes the various approaches based on the orthograde introduction of scaffolds or biomaterials (with or without cells) into the root canal to achieve pulp tissue regeneration. There are currently no systematic reviews investigating whether ETE is a suitable method for the treatment of endodontic disease in both mature and immature permanent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…These conclusions corroborate the previous work of Matoug‐Elwerfelli, stating that more appropriate in vitro and in vivo studies are necessary to ensure a predictable clinical outcome of REPs (Matoug‐Elwerfelli et al, 2021). These lackings also echo findings from reviews of clinical studies on REPs, where a lack of evidence is concluded by Ribeiro et al (2020) and Widbiller et al (2022) who state that further, well designed studies, both pre‐clinical and clinical that include comparison of classical procedures and NGAS are necessary to assess the efficacy of alternatives to CAS for REP (Widbiller et al, 2022).…”
Section: Discussionmentioning
confidence: 67%
“…These conclusions corroborate the previous work of Matoug‐Elwerfelli, stating that more appropriate in vitro and in vivo studies are necessary to ensure a predictable clinical outcome of REPs (Matoug‐Elwerfelli et al, 2021). These lackings also echo findings from reviews of clinical studies on REPs, where a lack of evidence is concluded by Ribeiro et al (2020) and Widbiller et al (2022) who state that further, well designed studies, both pre‐clinical and clinical that include comparison of classical procedures and NGAS are necessary to assess the efficacy of alternatives to CAS for REP (Widbiller et al, 2022).…”
Section: Discussionmentioning
confidence: 67%
“…For this guideline, a total of 14 systematic reviews (SRs) were conducted to support the guideline development process (Bucchi et al, 2022; Bürklein & Arias, 2022; Corbella et al, 2022; Donnermeyer et al, 2022; Hilmi et al, 2023; Jakovljevic et al, 2022; Meire et al, 2022; Meschi et al, 2022; Pirani & Camilleri, 2022; Plotino et al, 2022; Rossi‐Fedele & Ng, 2022; Rossi‐Fedele & Rödig, 2022; Tomson et al, 2022; Widbiller et al, 2022). Each SR has two designated senior reviewers, who were from different countries and institutions and were not established collaborators, to work together on each review.…”
Section: Methodsmentioning
confidence: 99%
“…Navigating the intricacies of infected developing teeth presenting necrotic pulp and apical periodontitis demands a sophisticated comprehension of inflammatory mechanisms and the dynamics between bioactive signals and the inflammatory milieu within the root canal system. This approach underscores the importance of integrating biomaterials science principles to facilitate targeted therapeutic interventions [6][7][8] . Caused by anaerobic polymicrobial infection, the pathoses results in a halt in root development and the formation of osteolytic apical lesions, including damage to associated periapical tissues such as cementum, periodontal ligament, and alveolar bone, leading to early tooth loss [9] .…”
Section: Introductionmentioning
confidence: 99%